What is social about social perception research? - Teufel, Christoph; von dem Hagen, Elisabeth; Plaisted-Grant, Kate C.; Edmonds, James J.; Ayorinde, John O.; Fletcher, Paul C.; Davis, Gregory (Frontiers in Integrative Neuroscience, 2013)
A growing consensus in social cognitive neuroscience holds that large portions of the primate visual brain are dedicated to the processing of social information, i.e., to those aspects of stimuli that are usually encountered in social interactions such as others’ facial expressions, actions and symbols. Yet, studies of social perception have mostly employed simple pictorial representations of conspecifics. These stimuli are social only in the restricted sense that they physically resemble objects with which the observer would typically interact. In an equally important sense, however, these stimuli might be regarded as ‘non-social’: the observer knows that they are viewing pictures and might therefore not attribute current mental states to the stimuli or might do so in a qualitatively different way than in a real social interaction. Recent studies have demonstrated the importance of such higher-order conceptualisation of the stimulus for social perceptual processing. Here, we assess the similarity between the various types of stimuli used in the laboratory and object classes encountered in real social interactions. We distinguish two different levels at which experimental stimuli can match social stimuli as encountered in everyday social settings: (i) the extent to which a stimulus’ physical properties resemble those typically encountered in social interactions and (ii) the higher-level conceptualisation of the stimulus as indicating another person’s mental states. We illustrate the significance of this distinction for social perception research and report new empirical evidence further highlighting the importance of mental state attribution for perceptual processing. Finally, we discuss the potential of this approach to inform studies of clinical conditions such as autism.